Multilayer dual-band bandpass filter / Mohamad Nasri Bakhtiar - Bakhtiar, Mohamad Nasri (2014)
This paper presents a dual-mode dual-band bandpass filter design using multilayer technology. The filter structure is based on parallel couple-line directly connected to a transmission line and parallel connected with another similar connection, creating a dualpath topology. The topology consists of characteristic impedances of the transmission line which is represented as Zr and even- and odd-mode characteristics impedance of the couple-lines, Zoe and Zoo. These impedances are the controlling parameter to control the dual-band filter response concentrating on the bandwidth and separation between the passbands. The multilayer technique improves the rejection-band and separation between the two passband, which is vital for a dual-band bandpass filter response. The filter was designed at 2 GHz using microstrip technology on FR-4. The result show the passband of the dual-band filter is centered at 1.59 GHz and 2.41 GHz. Simulated and measured result are presented throughout this paper to validate the design.